Variability of characteristics physiologic and anthropometric in practitioners of rugby in function of the category and position of game: Systematic revision of literature - Filipe Monteiro Pinheiro de Campos (Desafio Singular, 2008)
Objectives: Analyse the existence variability of anthropometric and physiologic characteristics in Rugby players according their game position and competitive level. Methodology: enhances the existence of significant variability in matter of different evaluation parameters subordinated to two ranges of characteristics anthropometric (weight, height, % of body mass and age) and physiologic (muscular power, maximum aerobic power, speed) according the practice status (professionals, semi-professional, amateur) and the position in game (forwards, backs). Results: they point with respect to clear differences the anthropometric and physiological level profile of the players, particularly when related to the competitive level. The level half-professional verifies a significant effect of the age in the corporal mass, muscular force, speed, agility and maximum aerobic capacity, with the physiological characteristics of the players to verify an increase in function of the increase of the game level. Conclusions: the results gotten in the different studies for amateur players do not demonstrate linearity what if it must in particular the games with low intensity, with frequency and regularity irregular, of short duration or based in training programs little structuralized or inappropriate. Parameters related with the agility, speed, muscular force and VO2máx present a gradual development in function of the increase of the age and the level the one that the game is practiced. On the other hand, in terms of the position assumed for the player in field, the physiological profile of professional players is similar wants if it deals with advanced wants well of defenses if that the anthropometric variations are in this field particularly well-known. In anthropometrics terms, the practitioners of Rugby present high muscular mass, being the players in the position of advanced older and more weighed than the defenses. Parallel to it, exists a significant effect of the age and level of game in the corporal mass. The stature differences are however less evidences than you ponder them.